BIPARENTAL CARE AND THE EVOLUTION OF MONOGAMY IN A PERUVIAN POISON FROG (RANITOMEYA IMITATOR: DENDROBATIDAE) - Tumulty, James (East Carolina University, 2012)
Selection for biparental care is considered to be an important factor in the evolution of monogamy if the value of exclusive cooperation in care for mutual offspring outweighs the benefits of polygamy for either sex. Support for this hypothesis has come primarily through parent removal experiments in avian taxa. We tested this hypothesis in the first known example of a socially and genetically monogamous amphibian, the mimic poison frog (Ranitomeya imitator), by conducting male removal experiments. Biparental care in R. imitator is characterized by egg attendance, tadpole transport, and the feeding of tadpoles with unfertilized trophic eggs. Our results show lower tadpole growth and survival for widowed females compared to control families. We demonstrate that in addition to egg attendance and tadpole transport, male parental care is critical for offspring survival throughout larval development. Previous research has shown the importance of female trophic egg provisioning of tadpoles in R. imitator. This, coupled with the results of the present study, supports the hypothesis that selection for biparental care has driven the evolution of monogamy in an amphibian.
Keywords: Animal behavior; Zoology; Evolution and development; Anurans; Biparental care; Mating systems; Monogamy; Parental investment; Ranitomeya imitator; Biology, Zoology; Dendrobatidae; Parental behavior in animals; Parental deprivation; Monogamous relationships